بیع و شراء پر اکراہ کے اثرات - Syed Bacha Agha (Pakistan Journal of Islamic Research)
It is obligatory upon every Muslim to learn the rules of business transactions to the extent of his need. It is obligatory upon the scholars ('Ulamaa’) to teach these rules to the people. It is recommended that the seller make no distinction between buyers in the price of a commodity nor be difficult nor swear (an oath). When the buyer regrets (the purchase) and seeks to cancel the transaction, (the seller should) accept the cancellation. Few necessary conditions must be fulfilled for a business transaction to be considered valid and binding in Islam. Both the buyer and the seller must willingly agree to all details of the transaction, due to the statement of the Prophet (PBUH):"Verily business transactions are only (valid) by way of mutual agreement.” Thus, someone being forced to buy or sell property invalidates the transaction; however there is an exception to this. Shaykh Saalih al-Fawzaan states, "And if someone was justly forced into a sale, then it is legitimate. An example of this is when a judge forces someone to sell his property to pay his debt". However In this paper discussed about the Islamic point "Ikra’h" and its effects on buying and selling.